The wind that swept Mexico : the history of the Mexican Revolution 1910-1942 - Brenner, Anita; Leighton, Georges R. (New York London : Harper & Brothers, 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Revolutionaire bewegingen; zapatisme; Mexico